Smart Maintenance for Human-Robot Interaction An Intelligent Search Algorithmic Perspective - Xing, Bo.; Marwala, Tshilidzi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This self-contained book, written by active researchers, presents up-to-date information on smart maintenance strategies for human-robot interaction (HRI) and the associated applications of novel search algorithms in a single volume, eliminating the need to consult scattered resources. Unlike other books, it addresses maintaining a smart HRI from three dimensions, namely, hardware, cyberware, and hybrid-asset management, covering problems encountered in each through a wide variety of representative examples and elaborated illustrations. Further, the diverse mathematical models and intelligent systems constructions make the book highly practical. It enables readers interested in maintenance, robotics, and intelligent systems but perplexed by myriads of interrelated issues to grasp basic methodologies. At the same time, the referenced literature can be used as a roadmap for conducting deeper researches.
Introduction to Human Robot Interaction -- Introduction to Smart Maintenance -- Introduction to Intelligent Search Algorithms -- Hardware Capacity - Beginning of Life Perspective -- Hardware Capacity  ̶ Middle of Life Perspective -- Hardware Capacity  ̶ End of Life Perspective -- Cyberware Capacity  ̶ Platform and Middleware Layers Perspective -- Cyberware Capacity  ̶ Applications Layer Perspective -- Cyberware Capacity  ̶ Energy Autonomy Perspective -- Human Capacity  ̶ Physiology Perspective -- Human Capacity  ̶ Biopsychosocial Perspective -- Human Capacity  ̶ Exposome Perspective -- Conclusion.
Keywords: Control engineering; Robotics; Automation; User interfaces (Computer systems).; Human-computer interaction; Artificial intelligence; Computational intelligence; Control, Robotics, Automation; User Interfaces and Human Computer Interaction; Artificial Intelligence; Computational Intelligence